The Effect of Counseling Based on Fordyce\'s Pattern of Happiness on the Anxiety of Women with Spontaneous Abortion - Batool Khodakarami; Fatemeh Shobeiri; Bayan Mefakheri; Alireza Soltanian; Hossein Mohagheghi (Hamadan University of Medical Sciences, 2019)
Introduction: Spontaneous abortion is the most common complication of pregnancy that leads to mental disorders such as anxiety. Considering the high prevalence and the consequences of anxiety and the effective role of midwives in women's mental support following abortion, complementary therapies such as counseling are important. The aim of this study was to determine the effect of counseling based on Fordyce's pattern of Happiness on the anxiety of women with spontaneous abortion. Methods: This randomized clinical trial recruited 72 women with spontaneous abortion referred to Fatemiyeh hospital in Hamadan based on inclusion criteria and they were randomly assigned to intervention (n=36) and control (n=36) groups. Data were collected through a demographic questionnaire and HADS. The intervention group was consulted for a total 8 sessions of 60 minutes during the first 72 hours after the abortion. The sessions were held twice a week which lasted4 weeks. Both groups were followed immediately after and one months after the intervention. Data were analyzed via descriptive and analytical statistic with SPSS16. Results: The findings showed that before the intervention, no significant difference was observed in the mean score of anxiety between intervention and control groups (P>0.05). After the intervention and one months later, the results showed a significant difference between the two groups on anxiety (P<0.001). Conclusion: Counseling based on the pattern of happiness can control anxiety in women with spontaneous abortion; therefore, it is recommended that this pattern be used as an effective and noninvasive intervention to control psychological problems of women with spontaneous abortion.